2011
DOI: 10.3171/2011.4.jns10377
|View full text |Cite|
|
Sign up to set email alerts
|

Phase I/IIa trial of autologous formalin-fixed tumor vaccine concomitant with fractionated radiotherapy for newly diagnosed glioblastoma

Abstract: The results of this study demonstrate that AFTV treatment concomitant with fractionated radiotherapy may be effective in patients with newly diagnosed glioblastoma. Further clinical testing is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…Our recent prospective study on the use of AFTV concomitant with FRT for management of newly diagnosed glioblastoma showed very promising results. 29) In the present analysis, the recurrence patterns did not differ between patients, who underwent chemotherapy or vaccine therapy, so both types of adjuvant management may have comparable efficacy in control of the tumor progression after initial treatment. However, systemic therapy in general may have rather limited effect on the recurrence pattern of glioblastoma, as distant failure was noted in 18% of patients in the temozolomide-based chemoradiotherapy group, and 23% of those ones in FRT only group.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Our recent prospective study on the use of AFTV concomitant with FRT for management of newly diagnosed glioblastoma showed very promising results. 29) In the present analysis, the recurrence patterns did not differ between patients, who underwent chemotherapy or vaccine therapy, so both types of adjuvant management may have comparable efficacy in control of the tumor progression after initial treatment. However, systemic therapy in general may have rather limited effect on the recurrence pattern of glioblastoma, as distant failure was noted in 18% of patients in the temozolomide-based chemoradiotherapy group, and 23% of those ones in FRT only group.…”
mentioning
confidence: 72%
“…Chemotherapy was omitted in 18 patients, but treatment with autologous formalin-fixed tumor vaccine (AFTV) concomitant with FRT was performed. 29) Follow-up evaluations were performed by the attending neurosurgeon, starting 2 weeks after completion of FRT, and scheduled every 2-3 months thereafter. Additional examinations were done if required by the clinical condition of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…Because of this, many cancer treatments use "whole-cell" vaccines prepared from resected tissue that contains the entire antigen spectrum for each patient's primary tumor (35)(36)(37). By enabling the immune system to react with unique epitopes, these vaccines can evoke reactions against an array of antigens that do not need to be preidentified by the physician.…”
Section: Discussionmentioning
confidence: 99%
“…The actuarial 2-year survival rate was 40%. These results demonstrate that vaccine treatment in combination with fractionated radiotherapy may be effective in patients with newly diagnosed glioblastoma (Muragaki, et al 2011). Since the previous pilot study with AFTV therapy only, also has shown a good response, the outcome of the phase I/IIa clinical trial might have been even better if it has been combined with hypo-fractionated radiation therapy as described in the previous paragraph 4.3.…”
Section: Treatment Of Newly Diagnosed Glioma With Fractionated Radiotmentioning
confidence: 82%